Inklusivitas Maqāṣid al-Sharī‘ah dalam Penyelesaian Sengketa Ekonomi Syariah yang Melibatkan Non-Muslim di Pengadilan Agama - Sherhan Sherhan (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This article aims to analyze the application of the principle of inclusivity and the values of maqāṣid al-sharī‘ah in the settlement of Sharia economic disputes involving non-Muslim parties before the Religious Courts, as well as to examine their relevance in achieving substantive justice. This study employs a normative juridical method using statutory, conceptual, and case study approaches through the analysis of legislation, court decisions, scholarly literature, and interview data. The findings reveal that the jurisdiction of the Religious Courts in resolving Sharia economic disputes is based on legal relationships arising from Sharia contracts and the principle of voluntary self-submission, rather than the religious identity of the parties. The application of this principle is consistent with the objectives of maqāṣid al-sharī‘ah, particularly in safeguarding property (ḥifẓ al-māl), upholding justice (al-‘adl), and promoting public welfare (maṣlaḥah) for all parties without discrimination. This study contributes by proposing an integrative model that combines the principle of inclusivity with maqāṣid al-sharī‘ah as a foundation for strengthening a more just, inclusive, and responsive Sharia economic dispute resolution system within the national legal framework.